1993
DOI: 10.1523/jneurosci.13-08-03193.1993
|View full text |Cite
|
Sign up to set email alerts
|

The retinal fate of Xenopus cleavage stage progenitors is dependent upon blastomere position and competence: studies of normal and regulated clones

Abstract: The clonal origin of the stage 43-44 Xenopus retina from cleavage stage precursors was quantitatively assessed with lineage tracing techniques. The retina descends from a specific subset of those blastomeres that form forebrain. The most animal dorsal midline cell (D1.1.1) produced about half of the retina, the three other dorsal ipsilateral blastomeres each produce about an eighth of the retina, and the four contralateral dorsal blastomeres and an ipsilateral ventral-animal cell together produce the remaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 28 publications
4
60
0
Order By: Relevance
“…It has been reported that a retinal area is 0.09 mm 2 and the number of RGCs is 2700 per retina in Xenopus tadpole at stage 45 (Gaze and Grant, 1992). From this observation, we estimated the distance between nearest RGCs to be 6 m. On the other hand, we estimated the diameter of an RGC of Xenopus tadpole at stages 43-44 to be 11 m based on the anatomical study of Huang and Moody (1993). Therefore, we set the distance between 6 and 11 m. We confirmed that the development of direction selectivity by a fast-moving white bar (see below) can also be reproduced with the distance 10 ͌ 2 m, which is Ͼ11 m (data not shown).…”
Section: Methodsmentioning
confidence: 98%
“…It has been reported that a retinal area is 0.09 mm 2 and the number of RGCs is 2700 per retina in Xenopus tadpole at stage 45 (Gaze and Grant, 1992). From this observation, we estimated the distance between nearest RGCs to be 6 m. On the other hand, we estimated the diameter of an RGC of Xenopus tadpole at stages 43-44 to be 11 m based on the anatomical study of Huang and Moody (1993). Therefore, we set the distance between 6 and 11 m. We confirmed that the development of direction selectivity by a fast-moving white bar (see below) can also be reproduced with the distance 10 ͌ 2 m, which is Ͼ11 m (data not shown).…”
Section: Methodsmentioning
confidence: 98%
“…Capped mRNAs were synthesized using Message Machine kit (Ambion). mRNAs for GFP (300 pg), β-galactosidase (β-gal; 200 pg) or Xenopus p15 Ink4b (1 ng; Open Biosystems) were injected in one dorsal animal blastomere at the eight-cell stage (Huang and Moody, 1993). Embryos were collected and staged according to Nieuwkoop and Faber (Nieuwkoop and Faber, 1967), and X-gal staining performed on β-gal-injected embryos as previously described (Turner and Weintraub, 1994).…”
Section: Construction Of δSet-ezh2 Microinjections Of Mrnas and Tranmentioning
confidence: 99%
“…Morpholinos against Ezh2 (ATG, 0.25 ng; UTR, 2.5 ng) or mRNA encoding ∆SET-Ezh2 (1 ng) were injected in one dorsal animal blastomere of 32-cell stage embryos along with 300 pg of GFP mRNA (Huang and Moody, 1993). GFP mRNA alone (300 pg) or control MO (0.5 ng) were injected as controls.…”
Section: Retinal Cell Fate Analysismentioning
confidence: 99%
“…3D,E). We tested whether the promotion of Müller cells by Sox2 could also occur at Sox2 levels that could inhibit proneural activity, by injecting Sox2 mRNA into one dorsal animal blastomere at the 32-cell stage [targeting over 60% of the retina (Huang and Moody, 1993) We also wondered whether the increase in Müller cells caused by Sox2 overexpression could be due to a weak phenocopy of a constitutive Wnt/β-catenin signaling effect, in that extra Sox2 might maintain the progenitor fate for longer, so that when these Sox2-transfected cells eventually differentiate, they do so in a glialpromoting late environment. After continuous BrdU administration from stage 32 to 40, only 10% of control Müller cells were BrdU negative, i.e.…”
Section: Sox2 Expression Also Inhibits Neuronal Differentiation In Thmentioning
confidence: 99%